CRITICAL MATHEMATICS EDUCATION AND INSTRUMENTATION FOR THE TEACHING OF MATHEMATICS: A SYSTEMATIC LITERATURE REVIEW IN A BACHELOR’S DEGREE PROGRAM - Oliveira, Bianca Aparecida Holm de; Brim, Juliana De Fátima Holm; Pinheiro, Nilcéia Aparecida Maciel; Junior, Guataçara dos Santos (Seven Editora, 2025)
This article presents a map on Critical Mathematics Education (CME), Teacher Training and Degree in Mathematics in Theses and Dissertations resulting from the research carried out at the CAPES Theses and Dissertations Base. To answer the research question: Is Critical Mathematics Education explored in the discipline of Instrumentation for Teaching Mathematics in the Degree in Mathematics in Higher Education? The methodological referrals followed the assumptions of a Systematic Literature Review through three moments. Initially, the productions referring to Critical Mathematics Education were selected, later a synthesis was elaborated in relation to the use of EMC in Teacher Training and finally in the Mathematics Degree course referring to the researched productions. The results point to different uses of CME in the undergraduate course of Licentiate in Mathematics, thus leading to a critical and reflective look at academics and future teachers.DOI: https://doi.org/10.56238/sevened2025.038-019